The PKU System: Development of Online UTHM Health Center Appointment System - Tan, Foo Yuan; Mostafa, Salama A. (Applied Information Technology And Computer Science, 2022)
Medical appointment is the process of schedule a formal arrangement for an individual to meet doctor at a particular time. UTHM Health Center is chosen as the case study in this project as it provides health and medical services for UTHM students. In this project, The PKU System was proposed to improve the appointment management process efficiency and reduce the time consumed for the process. The intended users of the system are UTHM students and health center staff. The system helps students to easily book appointments via online. The software development methodology that used to develop this project is object-oriented model due to fast development times and easy integration of existing software modules. The development of this system provides an online platform for the health center staff to manage the appointments applied by the students.